Vibrio alginolyticus is the pathogen of “Baotou” disease causing serious damage to Gracilariopsis lemaneiformis cultivation in China - Tong Pang; Feng Wang; Qunqun Guo; Mengjie Zhang; Yuanyuan Sun; Jianguo Liu (mBio)
ABSTRACT In recent years, a disease called “Baotou” has been causing large-scale yield reductions of Gracilariopsis lemaneiformis in China. Interestingly, Vibrio alginolyticus, which once reported to be a probiotic or pathogen for multiple marine organisms, was strongly proved to be the pathogen causing “Baotou” disease in this study. Analysis of 16S rRNA gene profiling revealed that V. alginolyticus was the most abundant and dominant bacterium on the algal thalli suffering from “Baotou” disease, whereas its presence was scarcely detected on healthy thalli. Scanning electron microscope (SEM) analysis revealed that a large number of V. alginolyticus cells were found to be attached to the algal thalli with “Baotou” disease and the rotten thalli acquired by the lab infection treatment. V. alginolyticus could cause the rotten symptoms which were consistent with those of “Baotou” disease. According to Koch’s postulates, V. alginolyticus was identified as the pathogen causing “Baotou” disease.IMPORTANCEA highly contagious disease known as “Baotou” disease has persistently triggered significant yield reductions in G. lemaneiformis throughout China. The pathogen of “Baotou” disease was isolated and identified as V. alginolyticus in this study. Interestingly, V. alginolyticus was once reported to be a probiotic to Saccharina japonica, and pathogen to Haliotis diversicolor, Paleopneustes cristatus, Ruditapes decussatus, and Litopenaeus vannamei. The study indicates that V. alginolyticus play a significant role in the competition or co-existence between G. lemaneiformis, S. japonica, abalone, sea urchin, bivalve, and shrimp.